ANALISIS KEBUTUHAN PENGEMBANGAN MODEL PEMBELAJARAN KIMIA DIRECT INSTRUCTION BERORIENTASI THINKING INDUCTIVELY UNTUK MENUMBUHKAN LIFE SKILL PESERTA DIDIK - Asih Widi Wisudawati (Chimica Didactica Acta)
This study aims to analyze the needs of students and teachers in the learning process chemicals to be used for the development of Direct Instruction model of teaching chemistry Thinking inductively oriented to foster students' life skill. This study population is the entire SMA / MA in Yogyakarta. The samples are purposive sampling determined by taking into account the achievement of learning outcomes. The study sample consisted of 2 (two) MA, 7 (seven) SMA, 2 (two) private high school. Data was gathered from observation, interview guidelines and questionnaires. analyzed descriptively and interpretative, equipped crosscheck the data and data sources. conclusions of this study (1) has identified three (3) learning model commonly implemented by teachers in the learning process chemistry, (2) some of the barriers / obstacles in applying the model of learning-oriented thinking inductively, (3) life skills students have developed the maximum.